Dexamethasone Causes Hypertension in Rats Even Under Chemical Blockade of Peripheral Sympathetic Nerves - Soto-Piña, Alexandra E.; Franklin, Cynthia; Rani, C. S. Sheela; Fernandez, Elizabeth; Cardoso-Peña, Elías; Benítez-Arciniega, Alejandra D.; Gottlieb, Helmut; Hinojosa-Laborde, Carmen; Strong, Randy (Frontiers in Neuroscience, 2019)
Synthetic glucocorticoids (GCs) are widely used to treat inflammatory conditions. However, chronic use of GCs can lead to hypertension. The cause of this undesired side effect remains unclear. Previously, we developed an in vivo rat model to study the mechanisms underlying hypertension induced by the chronic administration of the potent synthetic GC, dexamethasone (DEX) and found that the catecholamine biosynthetic pathway plays an important role. In the current study, we used this model to investigate the role of the adrenal medulla, renal nerves, and other peripheral sympathetic nerves in DEX-induced hypertension. After 5 days of baseline telemetric recording of mean arterial pressure (MAP) and heart rate (HR), rats were subjected to one of the following treatments: renal denervation (RDNX), adrenal medullectomy (ADMX), 6-hydroxydopamine (6-OHDA, 20 mg/Kg, i.p.) to induce chemical sympathectomy, or a combination of ADMX and 6-OHDA. On day 11, the animals received vehicle (VEH) or DEX in drinking water for 7 days, with the latter causing an increase in MAP in control animals. ADMX and RDNX by themselves exacerbated the pressor effect of DEX. In the chemical sympathectomy group, DEX still caused a rise in MAP but the response was lower (MAP of 6-OHDA/DEX < VEH/DEX, p=0.039). However, when MAP was normalized to day 10, 6-OHDA + DEX did not show any difference from VEH+ DEX, certainly not an increase as observed in DEX + ADMX or RDNX groups. This indicates that sympathetic nerves do not modulate the pressor effect of DEX. TH mRNA levels increased in the adrenal medulla in both VEH/DEX (p=0.009) and 6-OHDA/DEX (p=0.031) groups. In the 6-OHDA group, DEX also increased plasma levels of norepinephrine (NE) (p=0.016). Our results suggest that the activation of catecholamine synthetic pathway could be involved in the pressor response to DEX in animals even under chemical sympathectomy with 6-OHDA.